(untitled) (London Journal of Medical and Health Research, 2024)
The Maternal and Perinatal Death Surveillance and Response (MPDSR) is a system to identify, report and create mechanisms for reducing preventable maternal and neonatal deaths, and stillbirth. MPDSR has been implemented in Bangladesh in the last decade. This study was conducted to identify the factors including the barriers and enablers influencing the implementation of MPDSR within the existing health system in Bangladesh. We conducted a scoping review for literature published between 1999 to 2019. Two reviewers selected the articles based on a scoping review technique usingthe Prisma flow checklist and diagram. The articles were collected from search enginessuch as PubMed and Google scholar, and also from websites of public andprivate organizations, and United Nations (UN) Agencies.We synthesized the available evidence on barriers and facilitators of the current MPDSR process in Bangladesh. The search process identified 890 journal articles, 100 different guidelines and reports; 11 of them met the inclusion criteria for enablers and barriers of MPDSR implementation in Bangladesh. The enablers included interdisciplinary teamwork with good communication, capacity development, evidence from MPDSR review meetings leading to improvements in health services, coordination, and organized supervision and monitoring. The barriers included difficultiesincollecting data from hard-to-reach areas, ensuring the quality of data, limitationsinrecord keeping, social barriers, lack of effective coordination and planning for a timely response, limited human resources capacity, lack ofmotivation among the staff, varying levels of training and competence to identify complications, lack of supervision and poor implementation of guideline. The findings from this scoping review can guide policy makers in addressing and overcoming the barriers of MPDSR implementation in Bangladesh.